2022
DOI: 10.1186/s13148-021-01213-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation signatures associated with cardiometabolic risk factors in children from India and The Gambia: results from the EMPHASIS study

Abstract: Background The prevalence of cardiometabolic disease (CMD) is rising globally, with environmentally induced epigenetic changes suggested to play a role. Few studies have investigated epigenetic associations with CMD risk factors in children from low- and middle-income countries. We sought to identify associations between DNA methylation (DNAm) and CMD risk factors in children from India and The Gambia. Results Using the Illumina Infinium HumanMethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…These studies were performed on different ethnicities: Africans, East Asians, Europeans, Indian Asians, etc. 7–9,29–33 No obvious tissue-specific epigenomic pattern was revealed in these candidate CpG sites, which was confirmed by applying the eFORGE tool 34 (https://eforge.altiusinstitute.org/; Figure S3).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…These studies were performed on different ethnicities: Africans, East Asians, Europeans, Indian Asians, etc. 7–9,29–33 No obvious tissue-specific epigenomic pattern was revealed in these candidate CpG sites, which was confirmed by applying the eFORGE tool 34 (https://eforge.altiusinstitute.org/; Figure S3).…”
Section: Resultsmentioning
confidence: 64%
“…Many studies have investigated the associations between DNA methylation and BP and identified hundreds of associated 5′-cytosine-phosphate-guanine-3′ (CpG) sites. [6][7][8][9] However, different studies reported disparate results due to limitations in statistical power, sample sizes, and varying adjustments for important confounders, such as genetic background, which can lead to variability between studies. Twin studies have proven to be a valuable research tool in studying disease-related epigenetic changes, as the twin population is naturally matched for genetic and early-life environmental factors.…”
mentioning
confidence: 99%
“…Previous research highlighted the importance of epigenetics as a potential biomarker for screening, diagnosis, prognosis, and individualized treatment regimens [ 23 , 24 , 29 , 30 , 31 ]. DNA methylation (DNAm), a commonly studied epigenetic modification, has been associated with CVD [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 32 , 33 ] and cardiometabolic risk factors, mainly in adults [ 21 , 28 , 34 , 35 , 36 ]. Existing evidence showed that DNAm during early development was associated with obesity and CVD risk later in life [ 37 ]; early embryogenesis is a particularly sensitive time period for epigenetic alteration by environmental factors that may contribute to disease risk [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent European prospective cohort study reported a diet rich in methyl-donor nutrients, such as folate, vitamin B 12 , choline, methionine, and betaine, was associated with global methylation changes [26], which were linked to risks of cardiometabolic diseases among offspring [27]. Previously, an in vivo rat study showed that maternal methyldonor nutrient deficiency downregulated the gene expression of VDR and reduced the bioavailability of active VD [28].…”
Section: Introductionmentioning
confidence: 99%